2021
DOI: 10.1016/j.abd.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Main etiological agents identified in 170 men with urethritis attended at the Fundação Alfredo da Matta, Manaus, Amazonas, Brazil

Abstract: Background Sexually transmitted infections (STI) are a global public health problem. Urethritis are among the most common STIs, and can cause several complications and facilitate the transmission of the HIV virus. Objectives To investigate the main etiologic agents of urethritis in 170 men treated at Fundação Alfredo da Matta. Methods To identify the agents, urethral exudate and urine were collected. Gram and culture tests were performed in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…De Souza et al [ 23 ] investigated the presence of sexually transmitted bacteria in urethral swabs of 170 men by using conventional methods and molecular tests. The authors detected NG in 102 (60.0%), CT in 50 (29.4%), U. urealyticum in 29 (17.0%), MG in 11 (6.5%), U. parvum in 10 (5.9%), and M. hominis in 7 (4.1%) patients by the PCR method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Souza et al [ 23 ] investigated the presence of sexually transmitted bacteria in urethral swabs of 170 men by using conventional methods and molecular tests. The authors detected NG in 102 (60.0%), CT in 50 (29.4%), U. urealyticum in 29 (17.0%), MG in 11 (6.5%), U. parvum in 10 (5.9%), and M. hominis in 7 (4.1%) patients by the PCR method.…”
Section: Discussionmentioning
confidence: 99%
“…Single infection with NG, CT, and MG was reported in 46 (27.1%), 13 (7.6%), and 5 (2.9%) patients, respectively. The co-infection rate was 40.6%, and the most frequently detected co-infection was dual infection with NG and CT. As a result of the study, it was concluded that the rate of co-infection is high and molecular techniques are advantageous for the rapid and accurate diagnosis of the infections, which are crucial for both the treatment and prevention of STDs [ 23 ]. In 138 patients with urethritis included in our study, NG (5.8%), CT (13%), and MG (10.1%) were detected at higher rates, and the overall co-infection rate (4.1%) was approximately tenfold lower than that reported by de Souza et al [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 However, its potential for harm to the human body remains unclear. Some studies have shown that the rapid propagation of UU can cause pathological conditions such as genital tract infection, 3 genital tract blockage, 3 vaginitis, 4 cervicitis, 5 urethritis, 6 and prostatitis. 7 The latest research showed that UU is an important microorganism in the male reproductive tract and can affect the quality of sperm.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre essas situações, as Infecções Sexualmente Transmissíveis (ISTs) são um problema de saúde pública de abrangência mundial que têm provocado algumas das doenças mais comuns em circulação na sociedade e corroboram para o desenvolvimento de problemas de infertilidade, desenvolvimento de câncer, complicações na gravidez, morte ou infecção fetal e até mesmo problemas psicológicos e de convívio social atrelado ao estigma (Dias et al, 2021;Domingues et al, 2021). Dentre os principais agentes causadores das ISTs, podemos destacar os fungos, bactérias e protozoários, que têm sua disseminação facilitada, principalmente pela prática sexual sem a utilização de preservativos (de Souza et al, 2021;Gerhardt et al, 2008). Os fatores que contribuem para a transmissão contínua de ISTs nas populações são múltiplos, complexos e específicos ao contexto.…”
Section: Introductionunclassified